Response regulator–mediated MAPKKK heteromer promotes stress signaling to the Spc1 MAPK in fission yeast - Morigasaki, Susumu (The American Society for Cell Biology, 2013)
The Spc1 mitogen-activated protein kinase (MAPK) cascade in fission yeast is activated by two MAPK kinase kinase (MAPKKK) paralogues, Wis4 and Win1, in response to multiple forms of environmental stress. Previous studies identified Mcs4, a “response regulator” protein that associates with the MAPKKKs and receives peroxide stress signals by phosphorelay from the Mak2/Mak3 sensor histidine kinases. Here we show that Mcs4 has an unexpected, phosphorelay-independent function in promoting heteromer association between the Wis4 and Win1 MAPKKKs. Only one of the MAPKKKs in the heteromer complex needs to be catalytically active, but disturbing the integrity of the complex by mutations to Mcs4, Wis4, or Win1 results in reduced MAPKKK–MAPKK interaction and, consequently, compromised MAPK activation. The physical interaction among Mcs4, Wis4, and Win1 is constitutive and not responsive to stress stimuli. Therefore the Mcs4–MAPKKK heteromer complex might serve as a stable platform/scaffold for signaling proteins that convey input and output of different stress signals. The Wis4–Win1 complex discovered in fission yeast demonstrates that heteromer-mediated mechanisms are not limited to mammalian MAPKKKs.